THE DETERMINANTS OF GROWING AGRI-FOOD EXPORT: THE CASE OF CEE COUNTRIES - Balaban, Suzana; Joksimović, Marijana; Stoiljković, Bojan (Economics of Agriculture, 2022)
The aim of this study is to analyse the determinants of the growing agri-food export in the CEE countries. Using the SYS-GMM estimation, we control for the endogeneity problem. As the explanatory variables we use the variable that have been empirically proven as determinants of the agri-food export and available for observed countries. The obtained results show that the trade liberalisation increases the agri-food exports, while the EU enlargement indirectly affects the agri-food exports which is an important statement for policy-makers.